Targeting the endocannabinoid/CB1 receptor system for treating obesity in Prader–Willi syndrome - Knani, Ibrahim (Mol Metab, 2016)
OBJECTIVE: Extreme obesity is a core phenotypic feature of Prader–Willi syndrome (PWS). Among numerous metabolic regulators, the endocannabinoid (eCB) system is critically involved in controlling feeding, body weight, and energy metabolism, and a globally acting cannabinoid-1 receptor (CB(1)R) blockade reverses obesity both in animals and humans. The first-in-class CB(1)R antagonist rimonabant proved effective in inducing weight loss in adults with PWS. However, it is no longer available for clinical use because of its centrally mediated, neuropsychiatric, adverse effects. METHODS: We studied eCB ‘tone’ in individuals with PWS and in the Magel2-null mouse model that recapitulates the major metabolic phenotypes of PWS and determined the efficacy of a peripherally restricted CB(1)R antagonist, JD5037 in treating obesity in these mice. RESULTS: Individuals with PWS had elevated circulating levels of 2-arachidonoylglycerol and its endogenous precursor and breakdown ligand, arachidonic acid. Increased hypothalamic eCB ‘tone’, manifested by increased eCBs and upregulated CB(1)R, was associated with increased fat mass, reduced energy expenditure, and decreased voluntary activity in Magel2-null mice. Daily chronic treatment of obese Magel2-null mice and their littermate wild-type controls with JD5037 (3 mg/kg/d for 28 days) reduced body weight, reversed hyperphagia, and improved metabolic parameters related to their obese phenotype. CONCLUSIONS: Dysregulation of the eCB/CB(1)R system may contribute to hyperphagia and obesity in Magel2-null mice and in individuals with PWS. Our results demonstrate that treatment with peripherally restricted CB(1)R antagonists may be an effective strategy for the management of severe obesity in PWS.